A Student-Led, Multifaceted Intervention to Decrease Unnecessary Folate Ordering in the Inpatient Setting. Issue 5 (September 2019) - Goetz, Celine; Di Capua, John; Lee, Irene; Mei, Rena; Narula, Sukrit; Zarrin, Sarah; Poeran, Jashvant; Cho, Hyung J.
Abstract : ABSTRACT: To reduce unnecessary laboratory testing, a three-phase intervention was designed by students to decrease serum folate laboratory testing in the inpatient setting. These included an educational phase, a personalized feedback phase, and the uncoupling of orders in the electronic medical record. Average monthly serum folate ordering decreased by 87% over the course of the intervention, from 98.4 orders per month at baseline to 12.7 per month in the last phase of the intervention. In the segmented regression analysis, joint ordering of folate and vitamin B12 significantly decreased during the intervention ([INCREMENT]slope = −4.22 tests/month, p = .0089), whereas single ordering of vitamin B12 significantly increased ([INCREMENT]slope = +5.6 tests/month; p < .001). Our intervention was successful in modifying ordering patterns to decrease testing for a deficiency that is rare in the U.S. population.